Предмет: Математика, автор: amina2631

1 - a) 2(7 - a) b) 5x + 3 + 2(7 - x) c) 7 - 3(2 + C) d) 21y - (3 + y) 17 e) 2x + 25 + 3(x-7) - f) [(15 - 4x)2 - 9]2 - 40 g) 3[25 - x - 3(1 - y)] - 6 h) (2[5t + 2(15 - 3c] - k)} 7 + 3 i) (2x - [4 - y])5 - Z j) 3 - {2 [11 - 2(5 - 3c)] - 5t} + - -


помгите мне пожалуйста ​

Ответы

Автор ответа: SatoAki
0

Ответ:

Пошаговое объяснение:

a) 2(7 - a) = 14 - 2a

b) 5x + 3 + 2(7 - x) = 5x + 3 + 14 - 2x = 3x + 17

c) 7 - 3(2 + c) = 7 - 6 - 3c = 1 - 3c

d) 21y - (3 + y)17 = 21y - 51 - 17y = 4y - 51

e) 2x + 25 + 3(x - 7) = 2x + 25 + 3x - 21 = 5x + 4

f) {(15 - 4x)2 - 9]2 - 40 = (30 - 8x - 9)2 - 20 =(21 - 8x)2 - 20=42 - 16x - 20 = 22 - 16x

g) 3[25 - x - 3(1 - y)] - 6 = 3(25 - x - 3 + 3y) - 6 = 75 - 3x - 9 + 9y - 9 = 75 - 3x + 9y

h) (2[5t + 2(15 - 3c] - k)7 + 3 = (2(5t + 30 - 6c - k)7 + 3 = (10y + 60 - 12c - 2k)7 + 3 = 70k + 140 - 84c - 14k + 3 = 56k + 143 - 84c

i) (2x - (4 - y))5 - z = (2x - 4 + y)5 - z = 10x - 20 + 5y - z = 9z - 20 + 5y

j) 3-(2(11 -2 (5 - 3c)) - 5t) = 3-(2(11 - 10 + 6c) - 5t) = 3-(2(1 + 6c) -5t) = 3-(2 + 12c - 5t) = 3 - 2 - 12c + 5t = 1 - 12c + 5t


amina2631: спасибо
Похожие вопросы
Предмет: Алгебра, автор: zxcqweqwe